The Waste Management Approach for Water Settlement to Improve Quality of Life for Local Resident - Hew , Wooi Kean; Wan Mohamed, Wan Srihani (MAJ - Malaysia Architectural Journal, 2023)
Global climate change is predicted to cause an increase in sea level rise and the frequency and size of storm and storm surge. This willcontribute further to the shoreline erosion; flood damage, inundation of land salwater intrusion into the freshwater lens aquifer, among others. The special rapporteur observes that Malaysia is a high performer and that the accessibility of water and sanitation services is truly impressive. However, some groups still do not enjoy their human rights to water and sanitation as they collect water from surface sources that are often compromised in terms of quality and use inadequate sanitation services. There is no public awareness of the proper waste management approach and water pollution issue affected to the living environment. In this research, case study will be used as the research inquiry on the wastewater management approach for water settlement in order to improve the quality of life for local resident. However, this study only highlights the impact of climate change-induced inappropriate wastewater management and untreated water treatment on marine ecological living environments. The qualitative research data collection will be required in this case study to leads towards the archival analysis in the unit measurement and data collection strategies by using 12 number of interview questions generated from 2 deductive code and 2 sub-research question. This research will formulate wastewater treatment by using farming system to improve thesocial and econmy in this Pulau Ketam. The Majlis Perbandaraan Klang & Pulau ketam local community will be benefited and this research will formulate a new community farm house to improve the social and economic for local resident. Future research will conduct the qualitative research study on the effect of the wastewater management approach for water settlement in this Pulau Ketam.